2017
DOI: 10.1371/journal.pone.0186202
|View full text |Cite
|
Sign up to set email alerts
|

Effect of small-sided team sport training and protein intake on muscle mass, physical function and markers of health in older untrained adults: A randomized trial

Abstract: The effect of small-sided team sport training and protein intake on muscle mass, physical function, and adaptations important for health in untrained older adults was examined. Forty-eight untrained older (72±6 (±standard deviation, SD) years men and women were divided into either a team sport group ingesting a drink high in protein (18 g) immediately and 3 h after each training session (TS-HP, n = 13), a team sport group ingesting an isocaloric drink with low protein content (3 g; TS-LP, n = 18), or a control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 43 publications
2
19
0
Order By: Relevance
“…Average HR and time spent with HR above 90%HR max are somewhat lower in TsG than seen in several intervention studies using comparable activities [ 4 , 13 , 21 , 28 , 29 ]. A key difference between the present study and these studies is the smaller pitch size of 10 × 10 m. Some studies on untrained individuals have shown physiological effects after small-sided activities with small pitch sizes (~10 × 10 m) [ 22 , 30 ]. But a small pitch size limits the possibility of running with high speed, which may have caused the overall intensity to be lower than expected.…”
Section: Discussionmentioning
confidence: 92%
“…Average HR and time spent with HR above 90%HR max are somewhat lower in TsG than seen in several intervention studies using comparable activities [ 4 , 13 , 21 , 28 , 29 ]. A key difference between the present study and these studies is the smaller pitch size of 10 × 10 m. Some studies on untrained individuals have shown physiological effects after small-sided activities with small pitch sizes (~10 × 10 m) [ 22 , 30 ]. But a small pitch size limits the possibility of running with high speed, which may have caused the overall intensity to be lower than expected.…”
Section: Discussionmentioning
confidence: 92%
“…Thus, ingesting protein immediately and 3 h after small-sided ball training has been shown to promote gain in muscle mass in older individuals. 42 It is possible that muscle hypertrophy would have been induced if the subjects had ingested proteins after the floorball training during the follow-up period. However, the diet of the subjects in the floorball group was not controlled, nor was it recorded, so it remains unknown to what extent protein was ingested immediately after training sessions.…”
Section: Discussionmentioning
confidence: 99%
“…; Vorup et al . ). In women at older age, however, there are limited and conflicting data on a positive effect of exercise training on cardiac (Spina et al .…”
Section: Introductionmentioning
confidence: 97%
“…The main question we raise in this review is whether there may be a similar aspect of timing of exercise training after menopause: the exercise timing hypothesis. Regular exercise training is clearly beneficial for men at all ages and numerous studies have shown that men up to very old age profit from training in terms of vascular and cardiac function (Schmidt et al 2014;Vorup et al 2017). In women at older age, however, there are limited and conflicting data on a positive effect of exercise training on cardiac (Spina et al 1993;Egelund et al 2017) and vascular function (Pierce et al 2011a;Moreau et al 2013;Nyberg et al 2016;Seidelin et al 2017).…”
Section: Introductionmentioning
confidence: 99%